Interações e intervenções: a participação do artista contemporâneo em processos de reconfiguração sociais e espaciais - Rachel da Silva Falc?o Costa (2011)
This research investigates, analyses and confirms the active participation of the contemporary artist in social and spatial reconfiguration processes, from collaborative artistic practice, with emphasis on proposals of community-based art. Taking as initial motivation our personal involvement, as artist, in such practices, we set the analysis of issues that we consider essential and illuminating in such processes, which are: 1) The political dimension of aesthetic actions of the past rescuing, recovering and make possible to highlight references which are able to trace some of the genealogical links of current practices; 2) The aesthetic dimension of everyday issues trying to understand present artistic practices interest and range with respect to the common life, their events and their problems; 3) Ways of thinking (thoughts-actions) and ways of operating (action strategies) used by artists who chose to live art through interactions and interventions (experiences-actions) that are performed in a participatory and collaborative way in the social and physical environment built by man. We still dare to articulate the work of art (related to the collaborative artistic practices) with some philosophical concepts we believe contain in themselves the dynamism that moves these proposals toward the possible not yet performed. Theory and practice are added up each other to affirm the necessary adoption of an aesthetic stance (sensible) proposed by contemporary artist as the only able to lead to procedural, experiential and dialogical practices, that become effective as sharing and transdisciplinary creative and productive processes, guided by an integrative and holistic vision of life.